2015
DOI: 10.1016/j.jseaes.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The pre-Devonian tectonic framework of Xing’an–Mongolia orogenic belt (XMOB) in north China

Abstract: For citation : Hou H., Gao R., Kröner A., Zhang X., Zhang S., 2017. Discussion on the relationship between deep seismic reflection patterns and tectonic units of the eastern part of the Central Asian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
168
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(172 citation statements)
references
References 43 publications
1
168
0
3
Order By: Relevance
“…1a, Sengör et al, 1993;Sun et al, 2009;Zhou and Wilde, 2013;Xiao et al, 2015;Xu et al, 2015). It comprises subduction-accretion complexes, including voluminous juvenile granitoids and their extrusive equivalents, formed during the multiple events related to subduction of the Paleo-Asian Ocean during Paleozoic.…”
Section: Geological Backgroundsmentioning
confidence: 99%
“…1a, Sengör et al, 1993;Sun et al, 2009;Zhou and Wilde, 2013;Xiao et al, 2015;Xu et al, 2015). It comprises subduction-accretion complexes, including voluminous juvenile granitoids and their extrusive equivalents, formed during the multiple events related to subduction of the Paleo-Asian Ocean during Paleozoic.…”
Section: Geological Backgroundsmentioning
confidence: 99%
“…An understanding of the Paleozoic relationships between these microcontinental massifs and the North China Craton (NCC) is important for furthering our knowledge of the tectonic evolution and timing of final closure of the Paleo-Asian Ocean. Although recent studies have greatly enhanced our understanding of the Paleozoic evolution of the Paleo-Asian Ocean along the western segment of the northern margin of the NCC (Li et al, 2009;Li et al, 2014c;Ma et al, 2011;Xu et al, 2014;Yang et al, 2006;Zhang et al, 2014), less research has been conducted on the Paleozoic (especially late Paleozoic) tectonic evolution of the eastern segment of the northern margin of the NCC, and the sequence of tectonic events in the area remains controversial Pei et al, 2014;Wang et al, 2015b;Wang et al, 2015c;Xu et al, 2015). Some scholars, based on analyses of sedimentary sequences and paleontological evidence, have suggested that a passive continental margin existed along what is now the eastern segment of the northern margin of the NCC during the late Paleozoic (e.g., Hsu et al, 1991;Jia et al, 2004;Li, 1998;Xu et al, 2014;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2014Xu et al ( , 2015b proposed that this belt could be divided into five units ( Fig. 1b), including the Jiamusi, Songliao-Hunshandake, Xing'an-Airgin Sum, Erguna and Airgin Sum-Xilinhot blocks.…”
Section: Geological Settingmentioning
confidence: 99%